Province‐Wide Analysis of Patient‐Reported Outcomes for Stage IV Non‐Small Cell Lung Cancer. (17th July 2021) - Tjong, Michael C.; Doherty, Mark; Tan, Hendrick; Chan, Wing C.; Zhao, Haoyu; Hallet, Julie; Darling, Gail; Kidane, Biniam; Wright, Frances C.; Mahar, Alyson; Davis, Laura E.; Delibasic, Victoria; et al.
Abstract: Background: In Ontario, Canada, patient‐reported outcome (PRO) evaluation through the Edmonton Symptom Assessment System (ESAS) has been integrated into clinical workflow since 2007. As stage IV non‐small cell lung cancer (NSCLC) is associated with substantial disease and treatment‐related morbidity, this province‐wide study investigated moderate to severe symptom burden in this population. Materials and Methods: ESAS collected from patients with stage IV NSCLC diagnosed between 2007 and 2018 linked to the Ontario provincial health care system database were studied. ESAS acquired within 12 months following diagnosis were analyzed and the proportion reporting moderate to severe scores (ESAS ≥4) in each domain was calculated. Predictors of moderate to severe scores were identified using multivariable Poisson regression models with robust error variance. Results: Of 22, 799 patients, 13, 289 (58.3%) completed ESAS (84, 373 assessments) in the year following diagnosis. Patients with older age, with high comorbidity, and not receiving active cancer therapy had lower ESAS completion. The majority (94.4%) reported at least one moderate to severe symptom. The most prevalent were tiredness (84.1%), low well‐being (80.7%), low appetite (71.7%), and shortness of breath (67.8%). Most symptoms peaked at diagnosis and, while declining, remained high in the following year. On multivariable analyses, comorbidity, low income, nonimmigrants, and urban residency were associated with moderate to severe symptoms. Moderate to severe scores in all ESAS domains aside from anxiety were associated with radiotherapy within 2 weeks prior, whereas drowsiness, low appetite and well‐being, nausea, and tiredness were associated with systemic therapy within 2 weeks prior. Conclusion: This province‐wide PRO analysis showed moderate to severe symptoms were prevalent and persistent among patients with metastatic NSCLC, underscoring the need to address supportive measures in this population especially around treatments. Implications for Practice: In this largest study of lung cancer patient‐reported outcomes (PROs), stage IV non‐small cell lung cancer patients had worse moderate‐to‐severe symptoms than other metastatic malignancies such as breast or gastrointestinal cancers when assessed with similar methodology. Prevalence of moderate‐to‐severe symptoms peaked early and remained high during the first year of follow‐up. Symptom burden was associated with recent radiation and systemic treatments. Early and sustained PRO collection is important to detect actionable symptom progression, especially around treatments. Vulnerable patients (e.g., older, high comorbidity) who face barriers in attending in‐person clinic visits had lower PRO completion. Virtual PRO collection may improve completion. Abstract : Reporting a study in Canada, this article analyzes utilization of patient‐reported outcomes and symptom burden among patients with stage IV non‐small cell lung cancer, providing a basis for the development of strategies to address gaps in symptom management in this patient population.